Hubungan Faktor Demografi Dan Dukungan Sosial Dengan Depresi Pascasalin - Nurfatimah, Nurfatimah; Entoh, Cristina (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2017)
Postnatal depression is a mental disorder after the birth of her child and can last up to one year. Maternal postnatal mood disorder not an easy matter. The impact can be devastating life of the mother and her child. Currently there are many women who experienced postnatal depression but has not been detected. The purpose of this study was to analyze the relationship between demographic factors and social support in postnatal depression in The Working Area Of Puskesmas Kayamanya.The design of this research is cross sectional. Research subjects were followed for 56 respondents ranging from childbirth to 7 days postnatal. The samples was chosen by using consequtive sampling. The instruments used in this research are the Edinburgh Postnatal Depression Scale (EPDS) and standard social support questionnaire. The results reveal that the age is not significantly associated with depression postnatal (p = 0.514) and education (p = 0.154); but it is significantly parity (p = 0.012); economic status (p = 0.030), social support include the family (p = 0.035); friends (p = 0.017); and midwives (p = 0.005). The multivariate analysis reveals that midwifes support (wald=4,236; p= 0,04) is the dominant factor causing postnatal depression.